LOW-TEMPERATURE CO OXIDATION ON CU/V@H-BN (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
The catalytic oxidation of CO on Cu-embedded hexagonal boron nitride (h-BN) sheet is investigated using the firstprinciples method based on density functional theory. Cu atom embeds into the boron monovacancy with high stability and lower formation energy. There is about 0.48e charge transfer from Cu to the hexagonal boron nitride (h-BN) sheet according to the Hirshfeld charge population analysis and the adsorption energy is -5.90eV. The strong adsorption on the surface defect is accompanied by charge transfer to and from the adsorbate. The reaction proceeds via a two-step mechanism of CO + O → OOCO → CO2 + O and CO + O → CO2. The energy barriers of the former are 0.47 and 0.26eV respectively, while the latter is a process with energetic drop. The high activity of Cuembedded hexagonal boron nitride(h-BN) may be attributed to the electronic resonance among electronic states of CO, O2, and the Cu atom, particularly among Cu-3d, CO-2π*, and O2-2π* orbitals. This good catalytic activity opens a new avenue to fabricate catalyst of low-dimensional material for CO oxidation with lower cost and higher activity.